ELECTRO COAGULATION TREATMENT ON TANNERY BEAM HOUSE- SOAK LIQUOR BY HYBRID ELECTRODE COMBINATIONS (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Waste water released from beam house operation of soaking process contains different kind of pollutants such as protein, lipids, greases and hairs produce high amounts of Chemical Oxygen Demand and Biological Oxygen Demand. Mainly tannery industries in TamilNadu, India follow solar evaporation pans. The waste water coming from soaking process contains high amount of Chemical Oxygen Demand and chloride concentration. The research work focus on soak processing waste water coming out from tannery industry by Electro Coagulation process using different electrodes. The removal efficiency only determined for Chemical Oxygen Demand and compared by different anode/cathode combinations Al/Fe, Fe/Graphite, Pt/Fe and Fe/Zn investigated.